Risk Factors of Neonatal Sepsis at Perinatology Unit Sanglah General Public Hospital Denpasar - Kurniasih Widayati; Desak Putu Yuli Kurniati; Gusti Ayu Trisna Windiani (Universitas Udayana, 2016)
Background and purpose: Infant Mortality Rate (IMR) nationally in 2012 was 32 per 1000 live births and 29 per 1000 live births in Bali. This figure was higher than the target of the Millennium Development Goals (MDGs) in 2015 which amounted to 23 per 1000 live births. One of many factors that increase risk of infant mortality is neonatal sepsis. Research on neonatal sepsis has been done in Sanglah General Public Hospital but it was only a descriptive study. This study was conducted to determine the socio-demographic factors, clinical, environmental and invasive procedures associated with neonatal sepsis in the Sanglah General Public Hospital. Methods: The study design was a case control with a sample of 30 cases and 30 controls that were selected randomly by matching on birth month of the register book of 1 January to 31 December 2014 at the Perinatology Unit Sanglah Hospital. The case groups were patients who were diagnosed with sepsis, and the control groups were not the sepsis. Data were collected from medical records of patients using extraction form. Bivariate analysis was conducted to determine crude OR and multivariate logistic regression method to determine adjusted OR. Results: Bivariate analysis showed that factors that increase risk of neonatal sepsis were mothers who did not work or worked as laborers (OR=3.5; 95% CI: 1.1 to 11.7), low birth weight (LBW) babies (OR=6,6; 95% CI: 1.9 to 24.2), infant care in an incubator (OR=4.1; 95% CI: 1.2 to 14.3), infusion (OR=9.3; 95 % CI: 1.7 to 92.1) and the administration of oxygen (OR=7.0; 95% CI: 1.9 to 29.7). Multivariate analysis showed that the only variable significantly increases risk of sepsis was low birt weight (OR=20.2; 95% CI: 1.4 to 289.7). Conclusion: LBW was the risk factor of neonatal sepsis at Perinatology Unit, Sanglah General Public Hospital.